Somatostatin analog challenge test in the pre-surgical management of ACTH-secreting pheochromocytoma. (25th November 2019) - Rossini, Alessandro; Perticone, Francesca; Frosio, Laura; Schiavo Lena, Marco; Lanzi, Roberto
Abstract : Summary: ACTH-secreting pheochromocytoma is a very rare cause of Cushing's syndrome, with a high morbidity and mortality risk due to both cortisol and catecholamines excess. We report the case of a 45-year-old female patient with a 3 cm, high-density, left adrenal mass, diagnosed as an ACTH-secreting pheochromocytoma. The biochemical sensitivity of the tumor to somatostatin analogues was tested by a 100 μg s.c. octreotide administration, which led to an ACTH and cortisol reduction of 50 and 25% respectively. In addition to alpha and beta blockers, preoperative approach to laparoscopic adrenalectomy included octreotide, a somatostatin analogue, together with ketoconazole, in order to achieve an adequate pre-surgical control of cortisol release. Histopathological assessment confirmed an ACTH-secreting pheochromocytoma expressing type 2 and 5 somatostatin receptors (SSTR-2 and -5). Learning points: ACTH-secreting pheochromocytomas represent a rare and severe condition, characterized by high morbidity and mortality risk. Surgical removal of the adrenal mass is the gold standard treatment, but adequate medical therapy is required preoperatively to improve the surgical outcome and to avoid major complications. Somatostatin analogs, in addition to other medications, may represent a useful therapeutic option for the presurgical management of selected patients. In this sense, the octreotide challenge test is a useful tool to predict favorable therapeutic response to the treatment.